2008 IEEE Computer Society Conference on Computer Vision and Pattern Recognition Workshops 2008
DOI: 10.1109/cvprw.2008.4563017
|View full text |Cite
|
Sign up to set email alerts
|

Rotational flows for interpolation between sampled surfaces

Abstract: We introduce a locally defined shape-maintaining method for interpolating between corresponding oriented samples (vertices) from a pair of surfaces. We have applied this method to interpolate synthetic data sets in two and three dimensions and to interpolate medially represented shape models of anatomical objects in three dimensions. In the plane, each oriented vertex follows a circular arc as if it was rotating to its destination. In three dimensions, each oriented vertex moves along a helical path that combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This procedure is similar to organ segmentation except that the seed locations, rather than image intensities, are what drive deformation within the trained shape space describing day-to-day shape variations of the prostate [12]. The diffeomorphism implied by the two m-reps is then computed with a shape interpolation method called rotational flows [13]. The deformation is used to transform the planning image to generate an estimated treatment image for dose calculation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure is similar to organ segmentation except that the seed locations, rather than image intensities, are what drive deformation within the trained shape space describing day-to-day shape variations of the prostate [12]. The diffeomorphism implied by the two m-reps is then computed with a shape interpolation method called rotational flows [13]. The deformation is used to transform the planning image to generate an estimated treatment image for dose calculation.…”
Section: Methodsmentioning
confidence: 99%
“…In 3D cases, each oriented vertex moves along a helical path along the axis of rotation. It can be shown that the interpolation is shape-maintaining if the two objects are similar and is size-maintaining if the two models are congruent [13]. …”
Section: Methodsmentioning
confidence: 99%